2001
DOI: 10.1096/fj.00-0855fje
|View full text |Cite
|
Sign up to set email alerts
|

Administration of NF‐κB decoy inhibits pancreatic activation of NF‐κB and prevents diabetogenesis by alloxan in mice

Abstract: Many risk factors can trigger the development of insulin‐dependent diabetes mellitus (IDDM). The induction of IDDM in vivo is strongly associated not only with the generation of reactive oxygen species but also with the activation of the transcription factor nuclear factor‐κB (NF‐κB). The purpose of this study was to determine the role of NF‐κB activation in diabetogenesis. Alloxan, a diabetogenic compound that causes diabetic conditions by selectively killing the insulin‐producing pancreatic β‐cells, was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The underlying cause for this discrepancy is not entirely clear but could be due to differences in culture condition or cytokine treatment (12)(13)(14)(15). Indeed, most studies that found a proapoptotic function for NF-B used IL-1 or chemical toxins rather than TNF-␣ plus IFN-␥ to elicit islet cell death (17,18,20,21,44). We also confirmed a proapoptotic function for NF-B by using a combination of IL-1␤ plus IFN-␥.…”
Section: Discussionmentioning
confidence: 66%
“…The underlying cause for this discrepancy is not entirely clear but could be due to differences in culture condition or cytokine treatment (12)(13)(14)(15). Indeed, most studies that found a proapoptotic function for NF-B used IL-1 or chemical toxins rather than TNF-␣ plus IFN-␥ to elicit islet cell death (17,18,20,21,44). We also confirmed a proapoptotic function for NF-B by using a combination of IL-1␤ plus IFN-␥.…”
Section: Discussionmentioning
confidence: 66%
“…NF B (p50)-deficient mice had no resistance to the SHDS model of diabetes, indicating that, unlike alloxan (Quan et al 2001), streptozotocin's mechanism of direct -cell damage and destruction is not mediated by NF B. The decrease in the insulin content of the pancreas in p50-deficient mice treated with MLDS indicates that even subdiabetogenic doses of streptozotocin cause -cell destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive agents such as glucocorticoids, FK506 and cyclosporin A, used to prevent IDDM in animal models, have all been shown to inhibit NF B activation, along with their other actions (Beauparlant & Hiscott 1996). It has been reported that an NF B decoy oligodeoxynucleotide injected intravenously inhibits diabetogenesis and NF B activation by alloxan in mice (Grankvist et al 1981, Quan et al 2001. The activation of NF B and destruction of islet -cells by alloxan is, however, likely to be a direct effect of alloxan, which is an oxygen free-radical generator, and to have no autoimmune component.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate this point, experimental models of diabetes have been developed from which chemical induction with alloxan has been the most widely used (Rerup 1970). Administration of alloxan to different animals produces, via necrosis of the islets, several features common to those observed in human diabetes (Lukens 1948, Gaulton et al 1985, Quan et al 2001. There is some evidence that diabetics present a deficiency in mounting an inflammatory response, probably associated with severe reduction in insulin secretion rather than increased blood glucose levels (Garcia Leme et al 1973, Garcia Leme & Farsky 1993.…”
mentioning
confidence: 98%